Market Structure and Market Power in Selected Sectors of the Polish Economy Based on COICOP Classification - Pawel Uminski (Communications of International Proceedings, 2020)
This paper present new and simple measures of market structure and market power. Based on the classical models of market structures, where a given structure is determined by the number of enterprises, indexes of degree of monopoly have been estimated, representing an average number of entities per branch. Additionally, market power indexes have been determined as an average revenue per an enterprise in a given branch. This approach has been employed to the analysis of market structure and market power in the Polish economy in the period from 2001 to 2013, according to COICOP classification. The obtained results indicate that both market structures and market power of companies are quite diversified. Classes with large number of entities, e.g. Medical Services and low number of entities (Gas) could be indicated. Market power is also diversified – relatively low rates occurred in Medical Services class, while the highest rates were determined for Fuels class. The conclusions from the analysis imply that in many sectors with considerable market power, State Treasury is highly significant. Established measure of market power was compared with the well-known measures – Lerner's index and HHI. Correlation coefficients indicate that the relation is statistically significant but moderate or weak.
Keywords: Degree of Monopoly; Market Power; COICOP; Polish Economy.